Policies, principles, practices : new directions in foreign language education in the era of educational globalization - Cancino, Rita; Dam, Lotte; Jaeger, Kirsten (Cambridge Scholars Pub., 2011)
This book addresses the various challenges facing university foreign language teaching in non-anglophone countries in the era of educational globalization. Growing student mobility, net-based cross-border university education, and universities opening subsidiaries in other countries force university teachers to offer their teaching in English rather than in their mother tongue, and universities to equip their staff members with the necessary foreign language competencies. As a reflection of s ...
Keywords: Language and languages -- Study and teaching -- Social aspects.; Philology -- Study and teaching -- Social aspects.; Second language acquisition.; Langue seconde -- Acquisition.; Philologie -- Étude et enseignement -- Aspect social.; Language teaching & learning (other than ELT); English language teaching (ELT); Language teaching theory & methods.; FOREIGN LANGUAGE STUDY -- Multi-Language Phrasebooks.; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General.; LANGUAGE ARTS & DISCIPLINES -- Readers.; LANGUAGE ARTS & DISCIPLINES -- Spelling.; Language and languages -- Study and teaching -- Social aspects; Electronic book.